2016
DOI: 10.5958/0974-0279.2016.00053.7
|View full text |Cite
|
Sign up to set email alerts
|

Direction of Trade and Export Competitiveness of Chillies in India

Abstract: India is the world's largest producer and leading exporter of chilli in the global market. This paper has studied the direction of trade of chillies by Markov chain analysis and has shown that USA is the most stable market of chilli, followed by UAE and Sri Lanka, while Malaysia, Bangladesh and Pakistan are the unstable importers. The paper has found that during 2011-12, the major markets for Indian chilli were Malaysia (24.83%) and Sri Lanka (14.70%). The estimated NPCs have indicated that the Indian chilli w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…They had absorbed 100% share from Belgium and 79.96% share from Italy. Similar results were also found in the study conducted by Minten et al, 2014;Dev et al, 2016.…”
Section: Total Coffeesupporting
confidence: 91%
See 2 more Smart Citations
“…They had absorbed 100% share from Belgium and 79.96% share from Italy. Similar results were also found in the study conducted by Minten et al, 2014;Dev et al, 2016.…”
Section: Total Coffeesupporting
confidence: 91%
“…The conventional linear programming technique was used, as this satisfies the properties of transitional probabilities of non-negativity restrictions and row sum constraints in estimation. This method to estimate the coefficient of direction of trade was used in the many studies (Cariappa and Chandel, 2020;Dev et al, 2016;Haribabu, 2017;Mandanna, 1998;Pramod, 2007).…”
Section: Coffee Share In Agricultural Exports In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested the need for strategies to promote export of Indian coir to all the countries instead of dependence on very few countries. Devi et al [5] conducted a study to find out the direction of trade of chillies from India using Markov chain analysis. Data were analyzed for a period of seven years i.e., from 2004-05 to 2010-11.…”
Section: Kusuma and Basavarajamentioning
confidence: 99%
“…India is one of the leading producers and exporter of chilli and has a share of about 39.78% of the total world trade, but the productivity of chilli is low in India (1.75 t/ha) when compared to other countries, like Cape Verde, Jamaica, and Morocco, where the yield levels are higher than 10 t/ha [49]. Hence, it is important to increase the productivity of chillies in India.…”
Section: Introductionmentioning
confidence: 99%